Advancing Point-of-Care Ultrasound Training in Medical Schools: Ultrasound-Guided Subclavian Vein Access Training Using Formalin-Embalmed Cadavers. (25th April 2022) - Loveless, Bosten A.; Muir, Maxton W.; Limov, Abigail L.; Fritsch, Alexa R.; Thomas, Rebecca J.; Yancey, Taylor J.; Skidmore, Chad J.; Zapata, Isain; Nigh, Andrew D.; Mason, Nena Lundgreen
Abstract : OBJECTIVES: This brief report examines the feasibility of using formalin-embalmed cadavers in training medical students to use ultrasound guidance to access the subclavian. This novel educational approach is discussed in the context of the ongoing integration of point-of-care ultrasound training into medical education. Additionally, this report explores how cadavers can provide practical, effective, and hands-on skills training opportunities for medical students to learn to perform common clinical procedures under ultrasound guidance. DESIGN: This report presents subjective and objective data evaluating the utility of teaching medical students to perform ultrasound-guided subclavian vein access on formalin-embalmed cadavers. SETTING: Rocky Vista University College of Osteopathic Medicine in Ivins, UT. SUBJECTS: Twenty-five first-year medical students at Rocky Vista University. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Pre and posttraining questionnaires were administered to assess each participant's self-confidence in using ultrasonography to access the subclavian vein of a cadaver. A statistically significant increase in participant self-confidence was observed across all questionnaire items from pre to posttraining. Objective evaluation consisted of a supervised skills test. Participants were evaluated on their ability to visualize the subclavian vein with ultrasound and achieve flashback of blood/embalming fluid into a syringe. During skills testing, the number of needle sticks and the time taken to achieve flashback were recorded for each participant. Twenty-three of the 25 participants were able to successfully complete the skills testing assessment. CONCLUSIONS: The formalin-embalmed cadaver can be a readily available and effective learning tool for medical education programs seeking to provide training opportunities in ultrasound-guided clinical procedures. The use of cadavers allows learners to train in a low stress and anatomically authentic environment without risk of patient discomfort.